Fat-containing Retroperitoneal Lesions: Imaging Characteristics, Localization, and Differential Diagnosis - Shaaban, Akram M; Rezvani, Maryam; Tubay, Marc; Elsayes, Khaled M; Woodward, Paula J; Menias, Christine O (Radiographics, 2016)
The complex anatomy of the retroperitoneum is reflected in the spectrum of neoplastic and nonneoplastic conditions that can occur in the retroperitoneum and appear as soft-tissue masses. The presence of fat within a retroperitoneal lesion is helpful in refining the differential diagnosis. Fat is easily recognized because of its characteristic imaging appearance. It typically is hyperechoic at ultrasonography and demonstrates low attenuation at computed tomography (-10 to -100 HU). Magnetic resonance imaging is a more ideal imaging modality because it has better soft-tissue image contrast and higher sensitivity for depicting (a) microscopic fat by using chemical shift imaging and (b) macroscopic fat by using fat-suppression techniques. Whether a lesion arises from a retroperitoneal organ or from the soft tissues of the retroperitoneal space (primary lesion) is determined by examining the relationship between the lesion and its surrounding structures. Multiple imaging signs help to determine the organ of origin, including the "beak sign," the "embedded organ sign," the "phantom (invisible) organ sign," and the "prominent feeding artery sign." Adrenal adenoma is the most common adrenal mass that contains microscopic fat, while myelolipoma is the most common adrenal mass that contains macroscopic fat. Other adrenal masses, such as pheochromocytoma and adrenocortical carcinoma, rarely contain fat. Renal angiomyolipoma is the most common fat-containing renal mass. Other fat-containing renal lesions, such as lipoma and liposarcoma, are rare. Fatty replacement of the pancreas and pancreatic lipomas are relatively common, whereas pancreatic teratomas are rare. Of the primary retroperitoneal fat-containing lesions, lipoma and liposarcoma are common, while other lesions are relatively rare. (©)RSNA, 2016.